Elected or Appointed? How the Nomination Scheme of the City Manager Influences the Effects of Government Fragmentation - Sebastian Garmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Empirical work on the causal effect of government fragmentation finds diversified results. This might be explained by the fact that studies typically are settled in different institutional environments. To assess in how far the political system might shape the effects of fragmentation, this paper measures the causal effect of a change in the nomination scheme of the city manager on the council size effect. I utilize a combination of a Regression Discontinuity Design with a Difference-in-Difference Approach applied to a large panel data set of German municipalities. The paper finds that when the manager is appointed by the council, there is no significant council size effect, while there is negative effect when the manager is elected by the voters. This indicates that the political system indeed matters.
Keywords: C21; D72; H72; 330